Azerbaijan Republic : Joint Staff Assessment of the Poverty Reduction Strategy Paper. (IMF Staff Country Reports; Country Report, 2003)
This paper presents the Joint Staff Assessment of the State Program on Poverty Reduction and Economic Development 2003-2005 (SPPRED)-the first full Poverty Reduction Strategy Paper (PRSP) of Azerbaijan. The SPPRED represents a joint effort between the government and civil society in the country. There remain areas where progress needs to be made during the implementation and subsequent updates of the SPPRED. The poverty analysis has improved compared with the Interim Poverty Reduction Strategy Paper (I-PRSP).